A patient with pulseless ST elevation myocardial infarction caused by a very late stent thrombosis - Satoda, Masahiko; Yusa, Hiroaki (Journal of Cardiology and Cardiovascular Medicine, 2022)
Background: Persistent contrast staining is highly associated with stent thrombosis. Case summary: A 75-year-old woman presented with new-onset effort angina. A coronary angiogram revealed a 90% blockage of the distal left main trunk (LMT) and a 99% blockage of the ostial left anterior descending coronary artery (LAD). A 3.0 × 18-mm CYPHER™ the stent had previously been implanted into the dominant proximal circumflex artery (LCx) in 2009 because of unstable angina. The patient developed pulseless ST elevation myocardial infarction after the withdrawal of antiplatelet therapy before a scheduled CABG. The patient recovered with VA-ECMO and PCI using aspiration thrombectomy and urgent CABG. Discussion: This case highlighted that a preoperative patient may develop thrombosis at a previous stent site with peri-stent contrast staining and withdrawal of an antiplatelet regimen in certain settings poses an imminent risk for preoperative deterioration. A bridging strategy using intravenous PY12 inhibitor before CABG should be considered in this setting. The revascularization strategy should be selected based on coronary anatomy, hemodynamic status and baseline risk for CABG. A hybrid revascularization approach should be considered in this patient population.